2022
DOI: 10.3389/fsurg.2022.813123
|View full text |Cite
|
Sign up to set email alerts
|

The Hippo Signaling Core Components YAP and TAZ as New Prognostic Factors in Lung Cancer

Abstract: BackgroundThe Hippo pathway is an essential signaling cascade that regulates cell and organ growth. However, there is no consensus about (i) the expression levels of the Hippo signaling core components yes-associated protein (YAP) and transcriptional co-activator with PDZ-binding motif (TAZ) in lung cancer, especially in small cell lung cancer (SCLC), or (ii) their association with the prognosis of patients with SCLC.MethodsWe screened relevant articles and identified eligible studies in the PubMed, EMBASE, CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
(46 reference statements)
0
7
0
Order By: Relevance
“…Ma et al 42 reported that increased TOX3 expression might in pancreatic cancer patients was correlated with EMT and poor survival time. Jiang et al 43 summarized that the Hippo pathway is involved in carcinogenesis and progression of NSCLC and SCLC, and high expression levels of YAP and TAZ are independent and novel prognostic factors for lung cancer. EMT is emerging as a crucial target for anticancer therapy in combination with the agents eradicating tumor bulk 44 …”
Section: Discussionmentioning
confidence: 99%
“…Ma et al 42 reported that increased TOX3 expression might in pancreatic cancer patients was correlated with EMT and poor survival time. Jiang et al 43 summarized that the Hippo pathway is involved in carcinogenesis and progression of NSCLC and SCLC, and high expression levels of YAP and TAZ are independent and novel prognostic factors for lung cancer. EMT is emerging as a crucial target for anticancer therapy in combination with the agents eradicating tumor bulk 44 …”
Section: Discussionmentioning
confidence: 99%
“…RT is inevitably associated with radioresistance (RR). A search for prognostic factors in NSCLC has shown that high expression of Hippo pathway effectors is associated with decreased overall survival ( 7 ). Hippo pathway dysregulation ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, increased YAP expression and nuclear localization are responsible for EGFR inhibitors resistance [28]. In related meta-analysis, high expression level of YAP is associated with progression of NSCLC and is identified as an independent factors for poor prognosis [29]. And YAP is also a regulator of PDL1 in NSCLC (29,383,103).…”
Section: Introductionmentioning
confidence: 99%